The effectiveness of electroacupuncture in reducing postoperative pain, analgesic requirement and prevention of postoperative nausea and vomiting post total abdominal hysterectomy surgery - Seevaunnamtum, S Praveena D/O (2015)

(untitled)
Introduction: We explored the use of intraoperative single session low frequency ( 2 Hertz) electroacupuncture stimulation to show an opioid sparing effect whilst having better analgesic profile and reduction of postoperative nausea and vomiting (PONV) in patients recovering from hysterectomies. The tiny focused electrical current is postulated to modulate the pain pathway via release of endogenous opioid substances and stimulation of descending pain inhibitory pathways. Objectives: This was a prospective, double blinded randomized study of the effect of intraoperative electroacupuncture on postoperative pain, analgesic requirement and prevention of postoperative nausea and vomiting in patients scheduled for total abdominal hysterectomy with or without bilateral salphingo oophorectomy. The study was conducted in Hospital Raja Permaisuri Bainun, Ipoh. Methodology: Sixty four (64) women were randomly allocated to receive or not electroacupuncture. Electroacupuncture was started as a single continuous session started intraoperatively till the end of surgery. All patients received similar general anaesthesia and postoperative patient controlled analgesia morphine. Postoperative Numerical Rating Scale, incidence of nausea, vomiting and usage of rescue antiemetics at 30 minutes, 2 hours, 4 hours and 24 hours were recorded. Total morphine demand and usage were also recorded in first 24 hours. Assessment was by a blinded nursing staff. Data entry and analysis was conducted with PASW Statistics Data Editor(Statistical Package for Social Science SPSS Version 21) Results: Postoperative pain score was numerically lower in the electroacupuncture group with a significant reduction in the mean pain score at 30 minutes and 2 hours postoperation, showing a mean pain score of 2.75 ± (2.34) and 2.25 ± (1.80) (p value <0.05) respectively. In comparison, the mean pain score for the control group were 4.50 ± (2.37) and 3.88 ± (2.21) (p value < 0.05) respectively. The mean PCA morphine demand within 24 hours was significantly lower in electroacupuncture group showing 27.28 ± (21.61) times pressed as compared to the control group which recorded 55.25 ± (46.85) times pressed (p value < 0.05). The mean morphine dosage requirement within 24 hours showed a significant reduction in usage in electroacupuncture group showing a mean of 21.38 ± (14.38) mg as compared to the control group which recorded a usage of 33.94 ± (20.34) mg (p value < 0.05). Incidence of postoperative nausea was significantly reduced in electroacupuncture group at 30 minutes with a rate of 15.6% versus 46.9 % in control group (p value < 0.05). Conclusion: This study concludes that in subjects receiving electroacupuncture intraoperatively, there was a significant reduction in postoperative pain score up to the first 2 hours, decrease in morphine demand and requirement in the first 24 hours and reduction in incidence of postoperative nausea at 30 minutes postoperatively.